Comparison of the Medtronic SelectSecure and conventional pacing leads: Long‐term follow‐up in a multicenter pediatric and congenital cohort. Issue 3 (8th February 2019) - Moak, Jeffrey P.; Law, Ian H.; LaPage, Martin J.; Fish, Frank; Shatty, Ira; Dubin, Anne M.; Patel, Akash; Fishbach, Peter; Cain, Nicole; Johnsrude, Christopher; Berul, Charles I.; Bangoura, Aminata; et al.
Abstract: Introduction: The Medtronic SelectSecure™ (Minneapolis, MN, USA) pacing lead (SS) has theoretical advantages compared to conventional (C) transvenous pacing leads (PLs). The study purpose was to determine whether differences in electrical function and lead survival exist between these PLs in a large data set of pediatric and congenital patients. Methods: A multicenter historical longitudinal cohort study was performed comparing SS and CPL performance over a 72‐month follow‐up (FU). Ten centers provided data for both SS and CPL, matched for age, implanted pacing chamber, time period of implantation, and presence of heart disease. Results: The cohort consisted of 141 subjects in each group. No statistical differences were observed in age, gender, presence of heart disease, or pacing indication. Atrial and ventricular capture thresholds were stable throughout FU and higher in the SS group (atrial: 0.75 ± 0.02 vs 0.5 ± 0.04 V, ventricular: 1.0 ± 0.04 vs 0.75 ± 0.04 V), P < 0.001. Group PL sensing thresholds did not differ. The SS group required greater energy to pace (atrial: 0.57 ± 0.05 vs 0.32 ± 0.02 mJ, ventricular: 0.83 ± 0.05 vs 0.56 ± 0.06 mJ), P = 0.001. Early lead dislodgement and phrenic nerve stimulation were greater in the SS group (P = 0.03). Long‐term lead survival was high and similar between the two groups, P = 0.35. Conclusions: Long‐term survival of both PL was high with a low fracture rate. The SS had excellent electrical function but did show higher capture thresholds and increased energy to pace; these differences are offset by other advantages of the SS PL.